TINGKAT PENGETAHUAN PASIEN TENTANG PERAWATAN LUKA DIABETES MELITUS DI RUMAH SAKIT PTPN II BANGKATAN BINJAI TAHUN 2016 - Leli Herawati (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Diabetic wounds are injuries that occur in patients with diabetics involving disorders of the peripheral and autonomic nerves. Every year more than one million people with diabetes lose one of their legs as one of the complications of diabetes, this means that every 30 seconds one leg is lost due to diabetes somewhere in the world. The purpose of this study was to determine the level of knowledge of patients in the treatment of diabetes mellitus wounds in PTPN II Hospital Binjai Departure in 2016. The method of this study was descriptive observational. The population in this study were all patients treated at the Women's Room at PTPN II Bangkat Binjai Hospital, totaling 20 people. The sample in this study amounted to 10 people with accidental sampling techniques. The results of this study indicate that the Knowledge Level of Patients About Diabetes Wound Care in the Women's Room of PTPN II Hospital Binjai Departure in 2016 which is interpreted is good knowledge as many as 6 people (60%), enough as many as 2 people (20%) and less than 2 people (20%). 3. It is expected that patients will be able to prevent Diabetes Injuries by controlling blood glucose, using footwear, treating toenails, foot care and foot exercises. If Complications with Diabetes Injuries have occurred, the patient is expected to be able to treat diabetic wounds properly.Keywords: Patient Knowledge, Diabetes Melitus Wound Care